EVALUATION OF RHEOLOGICAL CHARACTERISTICS MIX DESIGN OF LATASTON (HRS-WC) BASED ON SPESIFICATION OF PUBLIC WORKS MINISTRY USING ASPHALT 60/70 PEN WITH ADDITION OF PURE ASBUTON - OCTRIYANA DJUNAEDI (NIM :26912319), RICO
Asbuton is a natural deposits asphalt, which Indonesia has in large volume, within in the rocks and soils in Buton Island. Asbuton is an opportunity to get an additive for improving asphalt to become stronger, more elastic and more durable if we mix Asphalt pen 60/70 and Pure Asbuton. The asphalt which has already been modified with Pure Asbuton (adding about 10% Pure Asbuton) then we test its Mechanistic Rheology with Dinamic Shear Rheometer (DSR). According to the result of DSR test, we can obtained the relationship between Time Sweep (t), Complex Shear Modulus (G*), Phase Angle (δ) and Strain (γ). The result of Marshall test shows that the Stability of Lataston (HRS-WC) Mixtures uses Asphalt Modified with 10% Pure Asbuton is higher than the mix uses Asphalt pen 60/70. This shows that the result of penetration test is equivalent with the result of Marshall test. According to the result of DSR test, the adding up of Pure Asbuton will make the value of Complex Shear Modulus becomes higher, however the value of Phase Angle (δ) becomes lower. After that, to determine the performance of Asphalt Modified with 10% Pure Asbuton in the mix, then we test the mix with Asphalt Mixtures Performance Tester (AMPT). Where the mix used is the gradation of HRS-WC (Lataston) using two variation of Asphalt, which are Asphalt pen 60/70 and Asphalt modified with 10% Pure Asbuton where we will get the result in the form of Dynamic Modulus (E*) for these two mixes. According to the result of AMPT, the value of Dynamic Modulus (E*) in the mix of Asphalt pen 60/70 is higher than the value of Dynamic Modulus (E*) in the mix of Asphalt Modified with 10% Pure Asbuton. It shows that the mix of Asphalt pen 60/70 is more elastic than the mix of Asphalt Modified with 10% Pure Asbuton.